Pengaruh Pendidikan Dan Pelatihan (Diklat), Promosi dan Kepuasan Kerja Terhadap Kinerja Pegawai di Sekretariat Daerah Kota Palembang - Purnamasari, Putri; Asteriniah, Femi; Febrianza, Muhammad (@-Publik: Jurnal Administrasi Publik, 2026)
This study was aimed to test the impact of Education and Training, Promotion and Job Satisfication towards Employee’s Performance In Regional Secretariat of Palembang City. This research includes quantitative research. The number of samples in this study were 40 employees in Regional Secretariat of Palembang City. The collection technique was done by using a questionnaire given a Likert scale score. The method of analysis used in this study is multiple regression analysis with Software SPSS Ver 23. The results of this study indicate that the education and training variable has a significant positive correlation to employee performance with a significance value of 0.006 less than 0.05, promotion has a significant positive correlation to employee performance with a significance value of 0.004 less than 0.05 and job satisfaction has a significant positive correlation to employee performance with a significance value of 0.000 less than 0.05.